Landscape waste composting with the aid of effective microorganisms using mechanical crusher machine - Muhamad, Mimi Suliza; Abdul Rahman, Muhammad Qusyairi; Hamidon, Nuramidah; Abdul Hamid, Nor Hazren; Mohamed Sunar, Norshuhaila; Harun, Hasnida; Ali, Roslinda (UTHM, 2020)
Malaysia is facing an uncontrolled increase in municipal solid waste generation due to population growth and nation development. Part of the waste that is disposed to landfill is landscape waste. The disposal of these waste can be reduced by composting method. In this study, the compost is produced by using a mechanical crusher machine for 1 hour and stored in a bin for weeks. The form compost had temperature and pH in the acceptable range for fertilizer but low moisture content. The C: N and C: P ratio is higher than the optimum range for fertilizer. The increased concentration of effective microorganisms leads to a higher content of C, N, and P, in which the maximum N content was obtained for sample C60 with 32.9 mg/L. While for P and K content was 11.32 mg/L and 77300 mg/L, respectively in sample A60. All the samples also show low heavy metals contents except for zinc.